TRANSFORMASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ERA KECERDASAN DIGITAL: ANALISIS KONSEPTUAL PENDEKATAN, KONTEN, DAN PERAN GURU - Dwi Adhi Widodo; Hadi, Syaiful (Almarhalah: Jurnal Pendidikan Islam, 2026)
This study aims to conceptually analyze how Islamic Religious Education (PAI) undergoes a significant transformation in the era of digital intelligence through changes in pedagogical approaches, content reconstruction, and the redefinition of the teacher’s role. The research is grounded in the urgent need to align religious education with rapid technological developments that have created a new learning ecosystem—one that is more flexible, interactive, and future-oriented. The research employs a descriptive qualitative method with a literature-based approach, reviewing books, journal articles, educational policies, and recent research reports related to educational digitalization and its integration into PAI instruction. The findings reveal three major themes. First, PAI pedagogy has shifted from traditional methods toward digitally integrated approaches that utilize artificial intelligence, interactive media, learning analytics, and collaborative digital learning models. These approaches enhance student engagement and the effectiveness of value transmission. Second, PAI content has undergone substantial reconstruction by incorporating emerging digital issues such as digital ethics, information security, academic integrity, media literacy, and character formation in virtual spaces. This ensures that Islamic values remain relevant to contemporary challenges. Third, the role of PAI teachers has significantly evolved from being mere transmitters of information to becoming facilitators of digital literacy, curators of learning resources, and guides in shaping students’ character and digital ethics. Teachers are now required to master digital tools while maintaining the humanistic dimension of learning. The study concludes that the transformation of PAI in the digital intelligence era is inevitable and requires simultaneous integration between pedagogical approaches, content development, and the evolving role of teachers. These findings are expected to inform policy development, curriculum design, and further research on the implementation of digitally integrated PAI instruction across different educational contexts.